Diagnóstico dos impactos da inserção de geração distribuída fotovoltaica na qualidade de energia elétrica em sistemas de distribuição - Silva, Eleandro Luis Marques da (2023)
With the increased penetration of distributed generation installations in Brazil's energy distribution systems, especially photovoltaic systems, much has been studied about the impacts on energy quality caused to the systems. The system, with large generators displaced from the load centers, has been modified by the presence of small generators, installed closer to the loads and spread throughout the distribution system. As a result, the change in the generation philosophies of Brazilian electrical systems has brought major challenges to the sector, especially distribution systems, which are, in the first instance, those that must absorb these impacts. This generation model close to the loads is causing major overvoltage problems at the coupling points, due to the reverse flow of active power. Problems such as increased technical losses are also reported in the literature. Therefore, in this dissertation, we seek to analyze the impacts caused to the systems from the point of view of energy quality. For this purpose, a real distribution feeder is being studied. Power quality measurements were carried out on a low voltage system. For the simulations, the impacts were evaluated using the OpenDSS software in Quasi-static time series mode for twenty-four hours on a real medium and low voltage feeder. Through the simulations and measurements carried out, it was possible to verify the impacts of overvoltage on medium voltage, but especially on low voltage. The occurrence of violations in the voltage transgression indicators established in the Distribution Procedures (PRODIST) was also noted. Regarding harmonic levels, no violations were identified in the systems. Other problems encountered were related to the power factor in the substation which, due to the high flow of active power inserted into the system, has consequences for adequate power levels. In relation to the capacity of the feeders, it was identified that, due to the “duck curve”, the need to resume power absorption by the system between 3 pm and 8 pm becomes abrupt, in many cases leaving a reverse flow for a high supply at this time.